(Effects Of Sodium Chloride And Barium Chloride During Water Distillation on The Quantity and Quality of Cumin oil (Cuminum Cyminum L)) - Sudibyo, Agus; -, Suprapto; Yusiana, Susi (Warta Industri Hasil Pertanian, 1990)
This report deals with studies both on the extraction of cumin oil from cumin seed (Curcumin cyminum L) using cohobation method and the effects of Sodium chloride (NaCL) or Barium Cuminum chloride (BaCl2) on the quantity and quality of cumin oil. It showed that the addition of Sodium chloride or Barium chloride at the 5,10,15 and 20 percent of concentration, increased the yield from 2.23 to 2.65 percent, specific grafity from 0.9281 to 0.9427 and the acid number from 3.14 to 6.44; but decreased the ester number from 27.80 to 19.00. Generally, however, the analysis result by means of Gas Chromatography showed that the purity and chemical component of cumin oil in each treatment given was not different